2011
DOI: 10.1111/j.1365-2044.2011.06763.x
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes in vascular surgical patients with isolated postoperative troponin leak: a meta-analysis

Abstract: SummaryAlthough peri-operative myocardial infarction remains a significant cause of morbidity and mortality following vascular surgery, the significance of an isolated troponin leak is uncertain. This is an elevation of troponin below the diagnostic threshold for a peri-operative myocardial infarction, without symptoms or ischaemic electrocardiography changes or echocardiography signs such as new regional wall motion abnormalities. This meta-analysis aimed to determine the early (< 30 days) and intermediate (<… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
43
0
4

Year Published

2012
2012
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 78 publications
(51 citation statements)
references
References 17 publications
4
43
0
4
Order By: Relevance
“…7 The reported incidence of PMI in vascular patients of between 5% and 26.5% 6,16 is comparable to the 24.3% found in our patients. The finding that PMI and a history of congestive cardiac failure were independent predictors of hospital mortality is consistent with the VISION 4 study.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…7 The reported incidence of PMI in vascular patients of between 5% and 26.5% 6,16 is comparable to the 24.3% found in our patients. The finding that PMI and a history of congestive cardiac failure were independent predictors of hospital mortality is consistent with the VISION 4 study.…”
Section: Discussionsupporting
confidence: 86%
“…A meta-analysis 6 showed that an isolated troponin leak was present in 10.2% of vascular surgical patients and 6.3% had a PMI, and both an isolated troponin leak and PMI were associated with an increased 30-day mortality. A peak postoperative troponin I (TnI) level above the URL has been significantly associated with increased mortality at 2.5 years following vascular surgery.…”
Section: Introductionmentioning
confidence: 99%
“…186,187,[207][208][209][210][211][212][213][214][215][216][217][218][219][220] The definition of an abnormal stress echocardiogram in some studies was restricted to the presence of new wall motion abnormalities with stress, indicative of myocardial ischemia, but in others also included the presence of akinetic segments at baseline, indicative of MI. These studies have predominantly evaluated the role of DSE in patients with an increased perioperative cardiovascular risk, particularly those undergoing abdominal aortic or peripheral vascular surgery.…”
Section: Dobutamine Stress Echocardiographymentioning
confidence: 99%
“…4 This study is but the latest in a series of investigations that have concluded that postoperative measurement of cardiac troponin is a better predictor of cardiac outcomes than preoperative-risk algorithms. [4][5][6][7][8] Intuitively, this link is not surprising. Surgery represents the ultimate physiologic stress test.…”
mentioning
confidence: 95%